Sweet Pepper Pests And Chemical Control Measures Against Them (Texas Journal of Agriculture and Biological Sciences, 2025)
This article presents the morphology and bioecology of the main pests of sweet pepper, spider mites, and greenhouse thrips. A chemical method of control against greenhouse thrips was used, in which Polo, 50% sus.c. (1.0 l/ha), Kapito, 50% em.c. (0.25 l/ha), and Desis, 2.5% em.c. (0.7 l/ha) were tested against the pest